THE APPLICATION OF FEMININE ENERGY AMONG GENERATION Z FEMALE INFLUENCERS ON SOCIAL MEDIA - Silaban , Sondang; Kartikawati, Dwi; Wardana , R Daniel Wisnu (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the application of Feminine Energy among Generation Z female influencers in constructing self-identity on social media. Feminine Energy is understood as an energy that embodies empathy, gentleness, and emotional balance, which has become a symbol of women’s empowerment (soft empowerment) in the digital era. This phenomenon is significant as it reflects a shift in the meaning of femininity from physical appearance toward self-awareness and personal authenticity. The research employs a qualitative approach, with data collected through in-depth interviews and observations of social media content produced by influencers who express Feminine Energy values. The analysis draws on Social Identity Theory (Tajfel & Turner, 1979), which highlights the processes of categorization, identification, and social comparison. The findings reveal that the application of Feminine Energy manifests in five key aspects: self-love, confidence, empathetic communication, calm emotional expression, and healthy personal boundaries. Through social processes, influencers internalize these values as integral parts of their personal and digital identities. In conclusion, Feminine Energy is not only a lifestyle but also a social identity strategy used by Gen Z female influencers to build an authentic, empowered, and reflective self-image in the digital space. Keywords : Feminine Energy, Social Identity, Influencers, Generation Z, Tiktok